Placental histopathology in preterm birth with confirmed maternal infection: A systematic literature review - Min, AM; Saito, M; Simpson, JA; Kennedy, SH; Nosten, FH; McGready, R (Public Library of Science, 2021)
Four in five neonatal deaths of preterm births occur in low and middle income countries and placental histopathology examination can help clarify the pathogenesis. Infection is known to play a significant role in preterm birth. The aim of this systematic review is to explore the association between placental histopathological abnormality and preterm birth in the presence of confirmed infection. PubMed/Medline, Scopus, Web of Science and Embase were searched using the keywords related to preterm birth, placental histopathology and infection. Titles and abstracts were screened and the full texts of eligible articles were reviewed to extract and summarise data. Of 1529 articles, only 23 studies (13 bacterial, 6 viral and 4 parasitic) were included, and they used 7 different gestational age windows, and 20 different histopathological classification systems, precluding data pooling. Despite this, histopathological chorioamnionitis, and funisitis (when examined) were commonly observed in preterm birth complicated by confirmed bacterial or viral, but not parasitic, infection. The presence of malaria parasites but not pigment in placenta was reported to increase the risk of PTB, but this finding was inconclusive. One in three studies were conducted in low and middle income countries. An array of: definitions of preterm birth subgroups, histological classification systems, histopathologic abnormalities and diagnostic methods to identify infections were reported in this systematic review. Commitment to using standardised terminology and classification of histopathological abnormalities associated with infections is needed to identify causality and potential treatment of preterm birth. Studies on preterm birth needs to occur in high burden countries and control for clinical characteristics (maternal, fetal, labor, and placental) that may have an impact on placental histopathological abnormalities.